Sistemas fotovoltaicos trifásicos com compensação de reativo, armazenamento interno de energia e inércia virtual - Souza, Arthur Costa de (2020)
Due to the increasing demand for energy, as well as the need to reduce greenhouse gas emissions that contribute to the increase of the greenhouse effect, the use of generation supplied by unconventional renewable sources, in order to maintain the reliability of the electrical system, has been noticeably increasing. Systems such as wind farms, solar farms and photovoltaic distributed generation, have been playing an important role in the Brazilian energy matrix because they are renewable sources of low environmental impact and have great unexplored potential in the country. However, these sources of energy considered as unconventional are characterized as intermittent sources as they depend heavily on weather conditions (wind and irradiance). Given this situation, battery energy storage systems have gained prominence for circumventing this limitation and providing other possibilities for the connection network. In this context, this thesis will model a photovoltaic generation system and evaluate the connection of this generation arrangement to the grid together with energy storage, in order to strengthen the voltage and frequency stability. The batteries will be used in the DC bus between the boost converter and the photovoltaic inverter. Therefore, a hybrid converter will be used to connect the battery bank to the DC bus. This thesis will also present a proposal to modify the control structures of a photovoltaic generation system, using the concept of virtual synchronous machine, to realize the effective control of the power flow and to contribute to voltage and frequency stability at coupling point. In addition, studies focusing on distributed photovoltaic generation with storage will be addressed, considering the impacts of this generation on the grid, regarding the effects of harmonic distortion, power factor and load relief.